SAT0554 Investigation of selected biochemical markers in knee osteoarthritis: the framingham osteoarthritis cohort. (15th June 2017) - Luo, Y; He, Y; Siebuhr, AS; Hoielt, S; Felson, D; Karsdal, M; Bay-Jensen, A-C
Abstract : Background: Osteoarthritis (OA) is a major cause of functional impairment and disability among the elderly. There is an unmet need for the development of biomarkers for identifying patients with high risk for OA and for monitoring drug efficacy. Specific and sensitive biochemical markers revealing the turnover of bone, cartilage, and synovial tissue may be useful for investigation and monitoring of OA. Objectives: To investigate a targeted set of five biochemical markers, which reflect joint tissue turnover, for their ability to evaluate the prevalence of radiographic and symptomatic knee osteoarthritis (OA) in a substudy from the cross-sectional Framingham OA cohort (FOA). Methods: The subjects from the community-based FOA cohort were divided up based on a terminology proposed by the FNIH-OAI consortium. Two main groups were defined: subjects with radiographic knee OA (RKOA, n=80) and a group with no radiographic OA (NRKOA, n=136). The presence of ROA as any Kellgren-Lawrence (KL) grade =2 or 3. The RKOA group were further divided into two groups; those with persistent symptoms of a joint (RKOA+S, n=30) and those without (RKOA-S, n=50). +S was defined as having pain, aching or stiffness in either knee on most days. Serum levels of C1M, CRPM and huARGS (matrix metalloproteinases cleaved type I collagen and C-reactive protein neo-epitopes, aggrecanase cleaved 374 ARGS neoepitope of aggrecan, Nordic Bioscience) were determined by ELISA. Serum levels of cartilage synthesis and degradation biomarkers, hsPro-C2 and hsAGNx-1 (procollagen type IIB N-terminal propeptide, aggrecanase cleaved TEGE 373 neoepitope of aggrecan, Nordic Bioscience) were measured by electrochemiluminescence immunoassay (ECLIA). Each measure was fisher transformed in order to be comparable across the biomarkers. The correlation between the biomarkers and covariates was assessed. The subjects of substudy were segregated into two groups based on the cut-off values of each biomarker. The cut-off values of these markers were set as mean of their reference levels. We used logistic regression to compare these two groups, and to examine the association between each marker and the presence of OA and/or pain. All confounding factors were adjusted. Results: The two main groups were well-matched by age, sex, and BMI. Two biomarkers correlated negatively with BMI: C1M and CRPM. Aggrecan degradation biomarker, hsAGNx-1 was negatively associated with age while the huARGS was not associated with it (Table 1 ). CRPM was associated with a lower risk of RKOA+S. Interestingly, hsPro-C2 was associated with a higher risk of it (Table 2). Conclusions: This study provides two major findings: 1) aggrecan degradation is not just aggrecan degradation and different neo-epitopes have distinct clinical relevance; 2) CRPM is a candidate biomarker of disease activity and for patient profiling. These data suggest a reference for interpretation of OA subject biomarker data in future human studies. Disclosure of Interest: None declared